Data Coming out of the Human Inhibitor PUP Study (HIPS) Reveal 4 Subgroups of Patients with Distinct Antibody Signatures - Gangadharan, Bagirath; Reipert, Birgit M; Berg, Verena; Scheiflinger, Friedrich; Blatny, Jan; Fijnvandraat, K; Gruppo, Ralph A.; Klintman, Jenny; Male, Christoph; McGuinn, Catherine E.; Meeks, Shannon L.; Radulescu, Vlad Calin; et al. (Blood, 2018)
Background and objectives FVIII inhibitors remain the major complication of replacement therapy in hemophilia A. Why some patients develop inhibitors whereas others do not is poorly understood. The Hemophilia Inhibitor PUP Study (HIPS, clinicaltrials.gov NCT01652027), a prospective multicenter observational study, aim to identify early immune biomarkers which predict inhibitor development in previously untreated patients (PUPs) with severe hemophilia A. Such biomarkers would facilitate early risk identification and the initiation of potential immune intervention strategies. Previously we reported time-resolved antibody data for the first 15 patients who completed antibody analysis (Gangadharan 2017). Here we present data from all 25 patients enrolled in HIPS, identifying four distinct patient subgroups based on their unique antibody signatures. We also summarize data for F8 mutations and longitudinal data of circulating immune cells such as FoxP3+ T cells (Tregs), Th17 cells, and granulysin+ cells. Methods FVIII inhibitor testing (Nijmegen method, performed in the central laboratory Medical University of Vienna) and antibody analytics were assessed prior to first exposure, 7-9 days after exposure day (ED) 1 and 5-7 days after EDs 5, 10, 20, 30, 40, and 50. FVIII-specific advanced antibody analytics were performed using methodology described by Whelan 2013 and Hofbauer 2015. FVIII mutational analysis was performed at Bloodworks Northwest, Seattle. Longitudinal epigenetic cell counting in whole blood using quantitative PCR-based methylation assays (www.epiontis.com) was done to monitor changes in peripheral FoxP3+ T cells (Tregs), pro-inflammatory Th17 cells, and granulysin+ cells. Results Our data reveal 4 different subgroups of patients associated with distinct signatures of FVIII-specific antibodies. The first subgroup includes 7 subjects who developed FVIII inhibitors by study criteria (B.U. > 0.6 B.U. x 2 measurements from consecutive study days in central laboratory). All 7 subjects had high-risk F8 gene mutations including large deletions (2), intron 22 inversions (4) and duplications (1). Inhibitors in these patients were associated with the development of high-affinity class-switched FVIII-specific antibodies which were detected prior to the first detection of inhibitors. High-affinity IgG1 was generally observed first, followed by high affinity IgG3 and subsequently high-affinity IgG4. Other isotypes and IgG subclasses of anti-FVIII antibodies were only seen occasionally. The second subgroup includes 2 subjects with low titer inhibitors. One subject, who expressed an intron 22 inversion, had a transient low titer FVIII inhibitor (1.4 BU/ml) which was associated with a high-affinity IgG1 antibody only. The other subject, who expressed a frame shift mutation, developed high affinity IgG1 by ED1. This patient had a low titer inhibitor detected (0.8 BU/ml) at ED20 which remained low (0.5 BU/ml) at study end, ED50. No other IgG subclasses were observed in either patient. The third subgroup includes 7 subjects with non-neutralizing antibodies. These subjects expressed intron 22 inversions (3), missense mutations (3) or an intron 1 inversion (1). Six of these patients developed low-affinity IgG1 antibodies which were observed until study end without the appearance of high-affinity antibodies or any other IgG-subclass. No FVIII inhibitors were detected at any time. The remaining subject initially developed low-affinity IgG1 antibodies and subsequently high-affinity IgG1 which remained until study end. No other IgG subclasses and no FVIII inhibitor were detected. The fourth subgroup includes 7 subject who never developed any FVIII-specific antibodies or FVIII inhibitors. These patients expressed missense mutations (3), an intron 22 inversion (1), a duplication (1), a frameshift mutation (1) or a nonsense mutation (1). Relative proportions of circulating FoxP3+ T cells (Tregs), Th17 cells or granulysin+ cells did not correlate with the development of FVIII inhibitors or FVIII-specific antibodies in individual PUPs. Conclusions Data obtained from the HIPS study identify four distinct patient subgroups based on their specific antibody signatures. Most importantly, high affinity class-switched antibodies preceded clinical inhibitor detection, substantiating their potential role as suitable predictive biomarkers for inhibitor development. Gangadharan:Shire: Employment. Reipert:Shire: Employment, Equity Ownership. Berg:Research Institute for Applied Bioanalytics and Drug Development, IMC Fachhochschule Krems /: Research Funding. Scheiflinger:Shire: Employment, Equity Ownership. Blatny:Shire, Pfizer, Roche: Consultancy, Speakers Bureau. Fijnvandraat:CSL Behring, Bayer, Shire: Membership on an entity's Board of Directors or advisory committees, Research Funding. Gruppo:Shire: Honoraria, Membership on an entity's Board of Directors or advisory committees. Male:CSL Behring: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Bayer: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Biotest: Speakers Bureau; Novo Nordisk: Speakers Bureau; Octapharma: Speakers Bureau; Roche: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau; Shire: Speakers Bureau; SOBI: Speakers Bureau. McGuinn:Shire: Research Funding; BioMarin: Consultancy; CSL Behring: Consultancy; Pfizer: Research Funding; Spark: Consultancy, Research Funding; Bioverativ: Membership on an entity's Board of Directors or advisory committees, Research Funding; Genentech: Consultancy. Meeks:HEMA Biologics: Other: Advisory Board; Genentech: Other: Advisory Board; Catalyst Biosciences: Other: Advisory Board; CSL Behring: Other: Advisory Board; Bayer: Other: Advisory Board; Bioverativ: Other: Advisory Board; Shire: Other: Advisory Board; Pfizer: Research Funding. Ragni:MOGAM: Membership on an entity's Board of Directors or advisory committees; Shire: Research Funding; Sangamo: Research Funding; SPARK: Consultancy, Research Funding; Novo Nordisk: Research Funding; Biomarin: Membership on an entity's Board of Directors or advisory committees, Research Funding; CSL Behring: Research Funding; Alnylam: Membership on an entity's Board of Directors or advisory committees, Research Funding; Bioverativ: Consultancy, Research Funding. Recht:Shire: Research Funding; Biogen: Research Funding; Novo Nordisk: Membership on an entity's Board of Directors or advisory committees, Research Funding; Kedrion: Membership on an entity's Board of Directors or advisory committees. Santagostino:Bayer, Shire, CSL Behring, Pfizer, Novo Nordisk, Grifols, Kedrion, Sobi, Bioverativ, Octapharma, Roche: Membership on an entity's Board of Directors or advisory committees, Speakers Bureau. Shapiro:Bayer Healthcare: Other: International Network of Pediatric Hemophilia; Octapharma: Research Funding; Prometic Life Sciences: Consultancy, Research Funding; Daiichi Sankyo: Research Funding; Novo Nordisk: Membership on an entity's Board of Directors or advisory committees, Research Funding; Genetech: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Bio Products Laboratory: Consultancy; Shire: Membership on an entity's Board of Directors or advisory committees, Research Funding, Speakers Bureau; Sangamo Biosciences: Consultancy; Kedrion Biopharma: Consultancy, Research Funding; Bioverativ, a Sanofi Company: Consultancy, Membership on an entity's Board of Directors or advisory committees, Research Funding; OPKO: Research Funding; BioMarin: Research Funding. Staber:NovoNordisk: Consultancy; Bayer: Honoraria; uniQure: Honoraria. Brown:Shire: Research Funding.